2012
DOI: 10.1111/j.1549-8719.2012.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Gut Region‐Specific Diabetic Damage to the Capillary Endothelium Adjacent to the Myenteric Plexus

Abstract: These data provide morphological, functional, and molecular evidence that the endothelial cells in capillaries adjacent to the MP is a target of diabetic damage in a regional manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 45 publications
3
31
0
8
Order By: Relevance
“…A recent study has shown that endothelial cells in the capillaries located close to the enteric neurons are damaged in diabetic animals, leading to change in the permeability of these capillaries and altered expression of adhesion molecules. The diabetes‐induced change in the capillaries of wall of the gut is not uniform within various segment of GI tract and has a distribution that resembles the distribution of changes in enteric neurons and nitrergic transmission . This evidence might suggest a role for endothelial dysfunction in pathogenesis of changes in ENS as a result of diabetes.…”
Section: Other Factors and New Directionsmentioning
confidence: 97%
“…A recent study has shown that endothelial cells in the capillaries located close to the enteric neurons are damaged in diabetic animals, leading to change in the permeability of these capillaries and altered expression of adhesion molecules. The diabetes‐induced change in the capillaries of wall of the gut is not uniform within various segment of GI tract and has a distribution that resembles the distribution of changes in enteric neurons and nitrergic transmission . This evidence might suggest a role for endothelial dysfunction in pathogenesis of changes in ENS as a result of diabetes.…”
Section: Other Factors and New Directionsmentioning
confidence: 97%
“…Motility changes secondary to hyperglycemia include increased peristaltic wave duration and decreased peristaltic velocity in the distal esophagus, decreased LES pressure, and delayed emptying of gastric contents . Dysmotility in diabetics may be due to gut‐specific damage to the capillary endothelium adjacent to the myenteric plexus …”
Section: Neuronal Changes Due To Hyperglycemiamentioning
confidence: 99%
“…Obesity, defined as a BMI >30 kg/m 2 , can decrease life expectancy and increase the risk of developing diabetes 27 Acute changes in glucose can slow gastric emptying De Boer et al 28 Acute hyperglycemia impairs esophageal peristalsis, reduces LES pressure, delays gastric emptying, slows intestinal transit, and reduces gallbladder contraction Bodi et al 29 Diabetics may experience gut-specific capillary damage that affects the myenteric plexus Esophageal dysmotility Kinekawa et al 30 GI reflux and esophageal motility worsen with long duration of diabetes Jorge et al 31 Diabetics experience changes in patterns of esophageal waves Ahmed and Vohra 32 Poor relaxation of LES and slow propulsive velocity were noted in diabetics Kinekawa et al 30 Esophageal motility disorder and abnormal acid reflux related to diabetic motor neuropathy Gastroparesis Fass et al 33 Multifactorial relationship between GERD and gastroparesis involves increased gastric volume, GE pressure gradient, and potentially provoked tLESr Obesity Hirata et al 34 Coexistence of metabolic syndrome and low adiponectin associated with higher prevalence of GERD Hormonal changes Kawahara et al 35 Rikkunshito may increase plasma ghrelin; used for GERD treatment in Japan Rubenstein et al 36 Ghrelin may have protective effect against GERD Nakamone et al 37 Hypomotilinenemia observed in diabetics; gastric emptying highly correlated with fasting plasma motilin levels GE, gastroesophageal; GERD, gastroesophageal reflux disease; GI, gastrointestinal; LES, lower esophageal sphincter; tLESr, transient LES relaxation.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%
“…Toluidinkék festés Az eljárás során 2 percig tartottuk a metszeteket festőoldatban (toluidin 1,75%, ecetsav 0,2 M, Na-acetát 0,2 M), majd 3x2 perces desztillált vizes mosás után 70%-os etilalkohol oldatban 3 perc differenciálás következett [164,165] . Fénymikroszkópia A képeket 40x,100x nagyítással Olympus (BX51) mikroszkóphoz kapcsolt digitális kamerával (Olympus DP11) készítettük.…”
Section: Fixálásunclassified
“…Morfometriai analízis A szövettani fotókat (40x, 100x nagyítás) a Scion image számítógépes programmal analizáltuk (B4.02. version, Scion Corp.) [164,165] .…”
Section: Fixálásunclassified